The difference of value of cash between financially constrained and unconstrained firms - Zeng, Zi-Yuan (2017)
Corporate cash holding，value of cash and financial constraints are always topical issues in academic studies. Since the cash holdings are so important for the operation and investment of companies, companies can allocate appropriate funds to support the operations and conduct profitable investments only with a good level of cash holding. In addition, holding sufficient internal funds can help firms to over the hump in future. This study investigates several measures, which are used for measuring the financial constraints. Besides, the impaction of cash holdings to firms under the circumstances of both financially constrained and unconstrained are discussed. On the purpose of classifying companies as constrained and unconstrained, we use four kinds of proxies, which are annual payout ratio, firm size, debt rating (long-term) and paper rating (short-term). The samples I use in this study include the data of firms in US market, which is available on Compustat's database over the period of 2000–2014. Through conducting the random effect model and GMM model, we find that financially constrained firms usually retain more cash than financially unconstrained firms and the impact of the cash is bigger for financially constrained firms. Furthermore, the firms without external fund resource will create more value with every extra dollar reserved and increase their marginal value of cash.